Community-Based Emergency Care: An Open Report for Nishnawbe Aski Nation - Ritchie, Stephen; Orkin, Aaron; VanderBurgh, Dave; Fortune, Melanie (2014)
This report summarizes the learnings of the Community-Based Emergency Care Roundtable, a two-day multi-jurisdictional meeting held in October 2013 in Sioux Lookout, Ontario. The purpose of this meeting was to discuss and address pre-nursing station emergency care needs in remote and isolated First Nation communities in Ontario. Representatives of First Nations’ governance and community organizations, Ontario Provincial and Canadian Federal governments, nursing and paramedical services, and non-governmental organizations joined together to develop shared understandings and a vision for the future of emergency care in remote and isolated settings. This report offers a Vision, Key Recommendations and Guiding Principles with which to improve emergency care for all injured and ill people in remote and isolated First Nation communities in Nishnawbe Aski Nation.